The Challenge of Cross- Language Interoperability. - CHISNALL, DAVID (Communications of the ACM, 2013)
The article discusses the challenge of interoperability between computer programming languages as of December 2013. It highlights the increase in difficulty of ensuring interoperability due to the increase in software complexity and decline in homogeneity among computer hardware products. The author says that at present the division between high-level languages and low-level languages no longer applies. The growing prevalence of domain-specific computer programming languages is also mentioned. Features and applications of object-oriented languages are also highlighted.